Analyses of Old “Prokaryotic” Proteins Indicate Functional Diversification in Arabidopsis and Oryza sativa - Singh, Anupama; Jethva, Minesh; Singla-Pareek, Sneh L.; Pareek, Ashwani; Kushwaha, Hemant R. (Frontiers in Plant Science, 2016)
During evolution, various processes such as duplication, divergence, recombination and many other events leads to the evolution of new genes with novel functions. These evolutionary events, thus significantly impact the evolution of cellular, physiological, morphological and other phenotypic trait of organisms. While evolving, eukaryotes have acquired large number of genes from the earlier prokaryotes. This work is focused upon identification of old “prokaryotic” proteins in Arabidopsis and Oryza sativa genome, further highlighting their possible role(s) in the two genomes. Our results suggest that with respect to their genome size, the fraction of old “prokaryotic” proteins is higher in Arabidopsis than in Oryza sativa. The large fractions of such proteins encoding genes were found to be localized in various endo-symbiotic organelles. The domain architecture of the old “prokaryotic” proteins revealed similar distribution in both Arabidopsis and Oryza sativa genomes showing their conserved evolution. In Oryza sativa, the old “prokaryotic” proteins were more involved in developmental processes, might be due to constant man-made selection pressure for better agronomic traits/productivity. While in Arabidopsis, these proteins were involved in metabolic functions. Overall, the analysis indicates the distinct pattern of evolution of old “prokaryotic” proteins in Arabidopsis and Oryza sativa.